2017
DOI: 10.3892/mmr.2017.6321
|View full text |Cite
|
Sign up to set email alerts
|

Berberine protects against diet-induced obesity through regulating metabolic endotoxemia and gut hormone levels

Abstract: Systemic inflammation, which can be induced by metabolic endotoxemia, and corresponding high-fat diet-mediated metabolic disorders are associated with gut microbiota. In the present study reverse transcription-polymerase chain reaction, immunofluorescence, pyrosequencing, ELISA and Oil Red O staining were performed to assess whether berberine can protect against diet-induced obesity, through modulating the gut microbiota and consequently improving metabolic endotoxemia and gastrointestinal hormone levels. Alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 46 publications
2
45
0
3
Order By: Relevance
“…As a traditional Chinese medicine, BBR has been used to treat diarrhea in China (Chen et al, 2015). Accumulating evidence suggests that BBR can improve metabolic syndrome by regulating glucose and lipid metabolism and attenuating insulin resistance (Kong et al, 2004;Zhang et al, 2014;Xu et al, 2017). Since BBR has low bioavailability, modulation of gut bacteria might be one possible mechanism for its antidiabetic and antiobesity effects (Han et al, 2011;Xie et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As a traditional Chinese medicine, BBR has been used to treat diarrhea in China (Chen et al, 2015). Accumulating evidence suggests that BBR can improve metabolic syndrome by regulating glucose and lipid metabolism and attenuating insulin resistance (Kong et al, 2004;Zhang et al, 2014;Xu et al, 2017). Since BBR has low bioavailability, modulation of gut bacteria might be one possible mechanism for its antidiabetic and antiobesity effects (Han et al, 2011;Xie et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A previous report showed that the BER improves diabetes by an enhanced insulin receptor (IRS) expression [35]. Thus, using by Western blot method, we measured the IRS phosphorylation levels at 30 min and the IRS expression levels at 8 days after the stimulation.…”
Section: Discussionmentioning
confidence: 97%
“…Previous study analyzed nine marker compounds—baicalin, wogonoside, baicalein, wogonin, glycyrrhizin, liquiritin, berberine, coptisine, and palmatine—in the BHSST extract using HPLC-PDA [ 9 ]. Baicalin [ 19 ], baicalein [ 20 ], glycyrrhizin [ 21 ], berberine [ 22 , 23 ], coptisine [ 24 ], and palmatine [ 24 ] have inhibitory effect of obesity in in vitro or in vivo study. In particular, Baicalin, the most abundant component in BHSST, was well known for having antiobesity effects.…”
Section: Discussionmentioning
confidence: 99%